PENDEKATAN HEALING ENVIRONMENT DALAM PERANCANGAN FASILITAS KESEHATAN MENTAL DI JOHAR BARU - Margareta Viannie Herwanto; Diah Anggraini (Jurusan Arsitektur dan Perencanaan, 2021)
Jakarta is a city that is growing rapidly with the development of settlements and infrastructure that continues to develop. A situation that demands an increase in the density of the city, as if leaving no place for its residents to breathe. People tend to be motivated to move functionally without having time to think about other activities such as interacting or socializing. There is an increasing number of cases of stress and depression experienced by residents of the city of Jakarta, especially those in low-income groups who live in dense settlements, such as in Johar Baru, Central Jakarta. While there is a close relationship between space and human psychological health, and how architecture can play a role in helping a person's healing process, through stimulation that triggers the release of hormones from the human brain as brain pharmaceuticals. This study aims to produce a concept and design of mental health facility buildings that can assist the community in preventing and coping with stress both on a community and individual scale. By using an environmental healing approach, the design will emphasize the direct and indirect connectivity between the environment, buildings and humans. So that it can support the healing process from feeling depressed, depressed and stressed by users.Keywords: healing architecture; urban stress; natural environment; public space Abstrak Jakarta merupakan kota yang berkembang pesat dengan pembangunan permukiman dan infrastruktur yang berkelanjutan. Suatu keadaan yang menuntut peningkatan kepadatan kota, seakan tidak menyisakan tempat bagi penduduknya untuk bernafas. Masyarakat cenderung beraktivitas secara fungsional tanpa sempat memikirkan aktivitas lain seperti berinteraksi atau bersosialisasi. Penduduk Kota Jakarta, terutama pada kelompok berpenghasilan rendah dan tinggal di permukiman padat, sebagaimana di Kelurahan Johar Baru Jakarta Pusat terdapat peningkatan jumlah kasus stress dan depresi. Antara ruang dan kesehatan psikologis manusia memiliki hubungan yang erat dalam proses pemulihan. Bagaimana arsitektur dapat berperan dalam membantu proses penyembuhan seseorang, melalui stimulasi yang mentrigger pelepasan hormon dari otak manusia sebagai brain pharmaceuticals. Studi ini bertujuan menghasilkan suatu konsep dan rancangan bangunan fasilitas kesehatan mental yang dapat membantu masyarakat dalam mencegah dan mengatasi stress baik dalam skala komunitas maupun individu. Dengan menggunakan metode healing environment, desain akan menekankan konektivitas baik secara langsung dan tidak langsung antara lingkungan, bangunan dan manusia. Sehingga dapat menunjang proses healing dari perasaan tertekan, depresi dan stress penggunanya.